The rare genus Myoplatypus (Coleoptera: Curculionidae: Platypodinae): three new species, new reports, and first records for South America - Kirkendall, Lawrence R.; Atkinson, Thomas H. (Zootaxa, 2023)
We describe three new species of Myoplatypus Wood, 1993: from Peru, Myoplatypus petrovi Kirkendall new species; from Honduras, M. quadricornis Kirkendall new species; from Nicaragua (M. nicaraguensis Kirkendall new species). We transfer Platypus biprorus Blandford, 1896 and Platypus sicarius Wood, 1971 into Myoplatypus, and we synonymize Platypus querceus Wood, 1971 with M. biprorus. The net result of these actions is a genus comprising nine tropical and one temperate American species. Males of all species are illustrated by photographs and a key to all species is provided. The collections reported here include the first South American records of Myoplatypus, a genus hitherto known only from North and Central America. Most Myoplatypus species are known from just one or a few collections and none of the tropical species are very widespread; only five tropical species have any known hosts (Quercus [Fagaceae] for three of them). The paucity of specimens could be because of peculiarities of biology that lead to them being under-collected (such as restriction to high elevations), but it also could be that they are narrow endemics, in which case these pinhole borer species deserve conservation attention. Nosotros describimos tres nuevas especies de Myoplatypus Wood, 1993: de Perú, Myoplatypus petrovi Kirkendall espécie nueva; de Honduras, M. quadricornis Kirkendall espécie nueva; de Nicaragua, M. nicaraguensis Kirkendall espécie nueva. Platypus biprorus Blandford, 1896 y Platypus sicarius Wood, 1971 se transfieren a Myoplatypus, y Platypus querceus Wood, 1971 se sinonimiza con M. biprorus Blandford. El resultado neto de estas acciones es un género que consiste en nueve espécies tropicales y una templada. Los machos de todas las especies están ilustrados con fotografías y se da una clave para todas las especies. Las colecciones reportadas aquí incluyen los primeros registros sudamericanos de Myoplatypus, un género hasta ahora conocido solo en América del Norte y América Central. La mayoría de las especies de Myoplatypus se conocen a partir de solo una o unas pocas colecciones y ninguna de las especies tropicales está muy extendida; sólo cinco especies tropicales tienen hospedadores conocidos (tres de ellos son robles). La escasez de especímenes podría deberse a algunas peculiaridades de la biología que los llevan a una recolección insuficiente (como la restricción a grandes alturas), pero también podría ser que sean endémicos estrechos, en cuyo caso estas especies de barrenadores merecen atención de conservación.